Theory and practice in the management of university championships organized in Hungary - Hédi, Csaba (Applied Studies in Agribusiness and Commerce, 2013)
After the 1989-1990 political changes the aim of the Hungarian University Sports Federation was to follow its traditions of nine decades in foreign policy as well, therefore the organization of international competitions in Hungary was promoted. Up to now the study of the management of these international events was neglected in the Hungarian scholarly literature, although all university sporting events held in Hungary were successful and they were highly appreciated internationally. Taking the example of three university world championships hosted by Hungarian towns, the objective of this paper is to analyze how the management succeeded to solve the major tasks of the organizational work and how some management theories were implemented in its activity. In order to collect data the following methods were used: analysis of documents, in-depth interviews and participant observation. The results are presented on the basis of some theses of the event planning theory, the event management theory, and the situational leadership theory. More specifically, the issues of motives-decisionactions, consistency- coherency- harmony and these of the quantity indicators of event organization in connection of the three underscored world championships organized in Hungary are discussed. In conclusion it is stated that in the management the situation theory had to be taken into consideration the most in the leading process. It was proven that despite preparations lasting often for several years and expanding to every detail of requirements, the flexibility of the management was crucial to search and to find response to every critical situation.